2012
DOI: 10.3130/aija.77.2789
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Design Assessments for the Relationship Between Urban Envelope and Snow Remove Energy Using Snow and Wind Simulations in Snowy and Cold Cities

Abstract: In the heavy snowy and cold cities, huge energy and cost have been spent for cleaning snow in urban area, especially in public area roads and pedestrian ways. It causes to the global warming, therefore cutting back on the emission of gases is required to the urban design in the snowy cities. Authors developed the block designs that reduce the snow accumulation on the public roads and pedestrian ways in downtown area Sapporo City, Hokkaido Japan. Four types of the block designs, individual developing type, unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Limited studies have been performed on the environmental influence of snow and wind in simulation tests using wind tunnels for urban design. Setoguchi and Watanabe et al considered the urban-design process, including snow and wind environmental assessments for winter cities [8][9][10][11][12][13][14][15]. These studies discussed models that were theoretically planned for developing desirable urban designs.…”
Section: Urban-design Process With Snow and Wind Simulations: A Studymentioning
confidence: 99%
“…Limited studies have been performed on the environmental influence of snow and wind in simulation tests using wind tunnels for urban design. Setoguchi and Watanabe et al considered the urban-design process, including snow and wind environmental assessments for winter cities [8][9][10][11][12][13][14][15]. These studies discussed models that were theoretically planned for developing desirable urban designs.…”
Section: Urban-design Process With Snow and Wind Simulations: A Studymentioning
confidence: 99%
“…The method of the snow simulations is the same as in a previous paper (Setoguchi (2012) 7) ). The snow simulation tests were carried out using the boundary-layer wind tunnel in the Hokkaido Research Organization Northern Regional Building Research Institute (HRO).…”
Section: Wind Tunnel For the Snow Simulation Testsmentioning
confidence: 99%
“…Setoguchi (2004) 3 7) discussed the urban design process including snow and wind environmental assessments for cities in severe winter areas, comparing high-rise buildings with medium-rise buildings, and showed that high-rise buildings have a more negative effect on the surrounding snow and wind conditions than medium-rise buildings. Based on the results of the above research, this paper focuses on medium-rise buildings in city blocks and discusses the effects of the snow and wind conditions based on the design form of city blocks (Table 1.).…”
Section: Tomabechi (2002)mentioning
confidence: 99%
“…By comparing high-and mid-rise buildings in Sapporo, Japan, [30,31] found that high-rise buildings more strongly impacted the surrounding snow and wind conditions than mid-rise buildings. Setoguchi et al [32] also proposed a method for estimating the amount of energy required for snow removal using their simulations. Setoguchi et al [28,29] discussed about the low-rise building design and Setoguchi et al [27,[30][31][32] and Watanabe et al [33] discussed about the medium-density buildings with 500-800% Floor Area Ratio (FAR).…”
Section: Building Design Urban Designmentioning
confidence: 99%
“…Anno [22] Smedley et al [23] Yukawa et al [24] Mitsuhashi [25] Yukawa et al [26] Setoguchi et al [27][28][29][30][31][32] Watanabe et al [33] Kim et al [15], Meng et al [19], Bosselmann et al [20] and Arens et al [21] produced useful studies of downtown San Francisco, California, United States, and they demonstrated the environmental impact of high-and mid-rise buildings using wind simulations conducted solely using a wind tunnel which compared San Francisco's wind conditions in 1985 and 2013 using a wind tunnel [15,[19][20][21]. Kim et al [15] suggested that the planning guidelines enacted since 1985 were effective in improving the wind comfort in public spaces.…”
Section: Building Design Urban Designmentioning
confidence: 99%